2017
DOI: 10.3389/fnbeh.2017.00002
|View full text |Cite
|
Sign up to set email alerts
|

Reconsolidation-Extinction Interactions in Fear Memory Attenuation: The Role of Inter-Trial Interval Variability

Abstract: Fear extinction typically results in the formation of a new inhibitory memory that suppresses the original conditioned response. Evidence also suggests that extinction training during a retrieval-induced labile period results in integration of the extinction memory into the original fear memory, rendering the fear memory less susceptible to reinstatement. Here we investigated the parameters by which the retrieval-extinction paradigm was most effective in memory updating. Specifically, we manipulated the inter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 38 publications
1
22
1
Order By: Relevance
“…Although others have demonstrated that postretrieval extinction can prevent fear relapse in animals (Auchter et al, 2017; Baker et al, 2013; Clem & Huganir, 2010; Flavell et al, 2011; Jones et al, 2013; Jones & Monfils, 2016; Monfils et al, 2009; Olshavsky et al, 2013; Rao-Ruiz et al, 2011; Shumake & Monfils, 2015) and in humans (Agren et al, 2012a, 2012b, 2017; Björkstrand et al, 2015; Golkar et al, 2017; Liu et al, 2014; Meir Drexler et al, 2014; Meir Drexler & Wolf, 2016a; Oyarzún et al, 2012; Schiller et al, 2010, 2013; Thompson & Lipp, 2017), it is important to consider that prevention of relapse may not equate to erasure of the fear memory. For example, a well-trained extinction memory may be able to outcompete a fear memory for expression, without the fear memory necessarily being eliminated (Lattal & Wood, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although others have demonstrated that postretrieval extinction can prevent fear relapse in animals (Auchter et al, 2017; Baker et al, 2013; Clem & Huganir, 2010; Flavell et al, 2011; Jones et al, 2013; Jones & Monfils, 2016; Monfils et al, 2009; Olshavsky et al, 2013; Rao-Ruiz et al, 2011; Shumake & Monfils, 2015) and in humans (Agren et al, 2012a, 2012b, 2017; Björkstrand et al, 2015; Golkar et al, 2017; Liu et al, 2014; Meir Drexler et al, 2014; Meir Drexler & Wolf, 2016a; Oyarzún et al, 2012; Schiller et al, 2010, 2013; Thompson & Lipp, 2017), it is important to consider that prevention of relapse may not equate to erasure of the fear memory. For example, a well-trained extinction memory may be able to outcompete a fear memory for expression, without the fear memory necessarily being eliminated (Lattal & Wood, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We propose a new analysis algorithm in which freezing data taken from the ITI during fear conditioning can be used to predict the stress susceptibility of subject animals to PTSD-like phenotypes. In fact, the ITI may play critical roles for several types of memories [36][37][38]. For instance, the duration of the ITI in the training procedure is inversely related to short-term memory recall [39].…”
Section: Discussionmentioning
confidence: 99%
“…A shorter ITI improves the learning performance of autistic children [40], but a longer ITI promotes a better performance for Pavlovian feature discriminations [41]. The ITI duration may also intervene in memory extinction, as subjects who received variable ITIs reinstated fear memory better than those receiving a xed ITI [38]. Despite the potential importance of the ITI, only behavioral features of the conditioned/unconditioned responses to stimuli have been examined, while those that occur during the ITIs have been largely ignored thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Study 2 used data from 215 subjects from two published studies [10,11]. Auchter et al [10] included 124 male Sprague-Dawley rats, acquired from Harlan (now Envigo) (250-300 g).…”
Section: Study 2 (A) Methods (I) Subjectsmentioning
confidence: 99%